Bahasa Inggris - Lestari, Anggun; Afandi; Ariyati, Eka (PendIPA Journal of Science Education, 2025)
The worsening environmental crisis in the 21st century demands citizen awareness and responsibility in maintaining the balance of the ecosystem. Ecological citizenship is an approach that emphasizes the role of individuals in understanding, preserving, and managing the environment in a sustainable manner. This study aims to analyze various approaches in integrating the concept of ecological citizenship into education as well as raising public awareness. The method used is a literature study by analyzing as many as 23 scientific articles from various journals through the Google Scholar search menu on the Publish or Perish (PoP) application. The results of the study show that education plays an important role in building ecological awareness both through formal, non-formal, and community-based education. Technological approaches such as Virtual Reality (VR) and digital platforms have proven effective in increasing ecological understanding, while social movements and environmental policies have also strengthened the implementation of this concept. However, there are still challenges such as low community participation, lack of policy support, and limited resources. Therefore, a collaborative strategy is needed between governments, educational institutions, and communities to strengthen effective and sustainable ecological citizenship.